Infusions of herbal blends as promising sources of phenolic compounds and bioactive properties - Finimundy, Tiane C. (2018)
Several plants have been used for medicinal applications and have been traditionally consumed as decoctions and infusions. Although some herbs are used alone as a beverage, they are often blended in mixtures to maximize their e ects. Herein, the nutritional characterization of six infusions from herbal blends was evaluated using the o cial methods of analysis (AOAC international). A further characterization of the individual phenolic profile was also performed by HPLC-DAD/ESI-MSn, and finally bioactive potential was determined by evaluating the antioxidant, cytotoxic, anti-inflammatory, and antimicrobial activities of each blend. The wide variety of plants in each sample led to variability in the results for all analyzed parameters. However, blends containing 15% Laurus nobilis L. and 15% Juglan regia L. in their composition showed higher sugar content and energy contribution; higher concentration of phenolic compounds (phenolic acids and flavonoids); greater antioxidant, cytotoxic, and anti-inflammatory capacity; and also better antimicrobial e ects against all the tested bacterial and fungal strains. Further studies will be necessary to evaluate the real synergistic e ects that these two species show in the presence of other plants, and to evaluate their potential for application in various food, pharmaceutical, and nutraceutical products as infusion preparations.